Oxaliplatin for the treatment of cisplatin-resistant cancer: A systematic review. - STORDAL, BRITTA KRISTINA (WB Saunders, 2007)
Oxaliplatin is widely regarded as being active in cisplatin-resistant cancer. We undertook a systematic review of the literature to identify, describe and critique the clinical and pre-clinical evidence for the use of oxaliplatin in patients with ?cisplatinresistant? cancer. We identified 25 pre-clinical cell models of platinum resistance and 24 clinical trials reporting oxaliplatin based salvage therapy for cisplatin-resistant cancer. The pre-clinical data suggests that there is cross-resistance between cisplatin and oxaliplatin in low-level resistance models. In models with high level resistance (>10 fold) there is less cross resistance between cisplatin and oxaliplatin, which may be a reason why oxaliplatin is thought to be active in cisplatin-resistant cancer. In clinical trials where oxaliplatin has been used as part of salvage therapy for patients who have failed cisplatin or carboplatin combination chemotherapy, there was a much lower response rate in patients with platinum-refractory or resistant cancers compared to platinum-sensitive cancers. This suggests that there may be cross-resistance between cisplatin and oxaliplatin in the clinic. Oxaliplatin as a single agent had a poor response rate in cisplatin refractory and resistant cancer. Oxaliplatin performed better in combination with other agents for the treatment of platinum resistant/refractory cancer suggesting that the benefit of oxaliplatin may lie in its more favourable toxicity and ability to be combined with other drugs rather than an underlying activity in cisplatin resistance. Oxaliplatin therefore should not be considered broadly active in cisplatin-resistant cancer.
Oxaliplatin in Cisplatin-Resistant Cancer
PUBLISHED
Keywords: Cisplatin; Oxaliplatin